THE USE OF FINTECH AS A MEDIATING VARIABLE OF FINANCIAL LITERACY ON THE DIGITAL SHOPPING BEHAVIOR OF GENERATION Z UNIVERSITY STUDENTS IN INDONESIA - Zeze Zakaria Hamzah; Mujito; Herman; Wahid Akbar Basudani; Vionita Qatrunnada (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the relationship between financial literacy, fintech usage, and digital shopping behavior among Generation Z university students in Indonesia, as well as the mediating role of fintech usage in this relationship. Data were collected from student respondents using purposive sampling and analyzed with path analysis. The results indicate that financial literacy significantly increases fintech usage, and fintech usage positively influences digital shopping behavior. The direct effect of financial literacy on digital shopping behavior becomes insignificant when fintech usage is included in the model, indicating that fintech usage fully mediates this relationship. These findings suggest that financial literacy encourages students to be more active in using fintech, and it is the intensity of fintech usage that drives their digital shopping behavior. This study highlights the importance of strengthening financial literacy and understanding financial technology to foster healthy financial behavior among students.